Pokémon. Sword & shield. Volume 10 - Kusaka, Hidenori; Tanzer, Molly (VIZ Media, 2024)
Casey Shield, a hacker who invented the Dynamax Simulator, and Henry Sword, a boy who repairs gear for Pokémon, both dream of entering the Galar region's Gym battles. For Casey, it's a chance to reunite with her lost Pokémon. For Henry, it's an opportunity to search for the legendary Rusted Sword and Rusted Shield.